1997
DOI: 10.1021/ma961467q
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of “Autoacceleration” in the Thermal Oxidative Polymerization of α-Methylstyrene

Abstract: Thermal oxidative polymerization of R-methylstyrene (AMS) has been studied at various temperatures (45-70 °C) and pressures (50-400 psi). Due to its high electron dense double bond, it undergoes thermal oxidative polymerization even at low temperatures fairly easily. The major products are poly(R-methylstyrene peroxide) (PMSP), and its decomposition products are acetophenone and formaldehyde. Above 45 °C the rate of polymerization increases sharply at a particular instant showing an "autoacceleration" with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
25
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 25 publications
3
25
0
Order By: Relevance
“…The saturation pressure of oxygen for styrene (STY) and α ‐methylstyrene (AMS) was found to be 2 and 300 psi, respectively 11. During the oxidative polymerization, STY shows auto‐deceleration with a break point, whereas AMS12 exhibits auto‐acceleration with the formation of a knee point 11. There are no reports on the effect of temperature and oxygen pressure on the oxidative copolymerizations, although some studies on the sequence analysis,10 kinetics and mechanism of their formation have been reported 1.…”
Section: Introductionmentioning
confidence: 99%
“…The saturation pressure of oxygen for styrene (STY) and α ‐methylstyrene (AMS) was found to be 2 and 300 psi, respectively 11. During the oxidative polymerization, STY shows auto‐deceleration with a break point, whereas AMS12 exhibits auto‐acceleration with the formation of a knee point 11. There are no reports on the effect of temperature and oxygen pressure on the oxidative copolymerizations, although some studies on the sequence analysis,10 kinetics and mechanism of their formation have been reported 1.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a peroxide polymer is formed in a high yield during the oxidative polymerization of styrene, but the simultaneous formation of benzaldehyde and formaldehyde is unavoidable and influences the polymerization kinetics and the reaction mechanism including a radical chain transfer. 8,12,27,28 The accurate evaluation of the thermal properties of peroxide polymers is often hin- dered by contamination with decomposition products despite a large number of studies on the synthesis and characterization of peroxide polymers.…”
mentioning
confidence: 99%
“…Interpolymerization of vinylic monomers with O 2 appears to be quite ubiquitous, as no compound containing the vinyl or vinylidene group has been found which does not readily form a peroxide upon exposure to air under ordinary conditions, which have all been found to initiate polymerization . Kishore et al reported the preparation of oligo(peroxide)s with O 2 of typical vinylic monomers, including nonsubstituted, monosubsttituted, 1,1‐disubstituted (vinylidene), 1,2‐disubstituted vinylics, and conjugated dienes form oligo(peroxide)s under the induction of ultraviolet (UV) light, visible light, heat or radicals, or catalysis of Co II complexes, in bulk or organic solvents, while Matsumoto successfully attempted the radical alternating oxidative polymerization of conjugated dienes with O 2 , leading to degradable poly(peroxide)s …”
Section: Introductionmentioning
confidence: 99%
“…Interpolymerization of vinylic monomers with O 2 appears to be quite ubiquitous, as no compound containing the vinyl or vinylidene group has been found which does not readily form a peroxide upon exposure to air under ordinary conditions, which have all been found to initiate polymerization. [ 7,8,13,14 ] Kishore et al reported the preparation of oligo(peroxide)s with O 2 of typical vinylic monomers, including nonsubstituted, monosubsttituted, 1,1-disubstituted (vinylidene), 1,2-disubstituted vinylics, and conjugated dienes form oligo(peroxide)s under the induction of ultraviolet (UV) light, visible light, heat or radicals, or catalysis of Co II complexes, in bulk or organic solvents, [15][16][17][18][19][20][21][22][23][24][25][26][27] while Matsumoto successfully attempted the radical alternating oxidative polymerization of conjugated dienes with O 2 , leading to degradable poly(peroxide) s. [28][29][30][31][32][33] Although oligo(peroxide)s might be candidates to initiate further polymerization of common vinylics under thermal or UV induction, [34][35][36][37] autopolymerization directly initiated by in situ formed oligo(peroxide)s upon air exposure appears as yet rather diffi cult under ordinary conditions. Due to the low concentration of O 2 in most organic solvents or monomers (≈10 −4 mol L −1 at ambient temperature upon exposure to air atmosphere) [ 38 ] as well as a delicate equivalence between formation and decomposition of peroxides, the build-up concentration of oligo(peroxide)s falls into a very low regime.…”
Section: Introductionmentioning
confidence: 99%